2021
DOI: 10.1080/15438627.2021.1895781
|View full text |Cite
|
Sign up to set email alerts
|

External and internal loads during the competitive season in professional female soccer players according to their playing position: differences between training and competition

Abstract: The aim of this study was to compare external (EL) and internal loads (IL) during training sessions compared to official matches in elite female soccer players according to their playing position. Training and match data were obtained during the 2017/18 season from eighteen players (age: 26.5±5.7 years; height: 164.4±5.3 cm; body mass: 58.56±5.58 kg) from a first Division Spanish team. The EL (total distance covered; high speed running distance; number of accelerations and decelerations) was assessed with a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 32 publications
9
49
0
Order By: Relevance
“…Translated to women's soccer, that would mean if total distances during matches were ∼7 km (youth), ∼9 km (college), or ∼11 km (professional/elite), then total weekly volume should roughly be 14-18, 18-22, and 22-28 km, respectively. These theoretical targets for total weekly training distance seem to be somewhat aligned with what has been reported for professional teams (∼16-22 km, exclusive of matches) (Mara et al, 2015b;Moraleda et al, 2021). Please note, the ratio (2.0-2.5X) would only be applied to total volume since evidence-based recommendations on other metrics (i.e., sprint distance, volume of accelerations, metabolic power) do not currently exist.…”
Section: Practical Considerations and Applicationssupporting
confidence: 68%
See 3 more Smart Citations
“…Translated to women's soccer, that would mean if total distances during matches were ∼7 km (youth), ∼9 km (college), or ∼11 km (professional/elite), then total weekly volume should roughly be 14-18, 18-22, and 22-28 km, respectively. These theoretical targets for total weekly training distance seem to be somewhat aligned with what has been reported for professional teams (∼16-22 km, exclusive of matches) (Mara et al, 2015b;Moraleda et al, 2021). Please note, the ratio (2.0-2.5X) would only be applied to total volume since evidence-based recommendations on other metrics (i.e., sprint distance, volume of accelerations, metabolic power) do not currently exist.…”
Section: Practical Considerations and Applicationssupporting
confidence: 68%
“…There is substantially more evidence describing the locomotor demands of elite female soccer with a fairly even distribution between professional (domestic) (Krustrup et al, 2005;Mohr et al, 2008;Andersson et al, 2010;Bradley et al, 2014;Datson et al, 2017;Mara et al, 2017b;Nakamura et al, 2017;DeWitt et al, 2018;Vescovi and Falenchuk, 2019;Julian et al, 2020;Scott et al, 2020a;Moraleda et al, 2021;Principe et al, 2021) and international matches (Mohr et al, 2008;Andersson et al, 2010;Ritschard and Tschopp, 2012;Hewitt et al, 2014;Martínez-Lagunas and Scott, 2016; Trewin et al, 2018a,b;Ramos et al, 2019;Bradley and Scott, 2020;Scott et al, 2020a,b).…”
Section: Professional and Internationalmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was confirmed that some of these tests may reflect the in-game running outputs in first Division league Portuguese women soccer players [ 31 ], thus suggesting that a systematic discrepancy in game demands depending on player position would not be so evident in females, which could be observed in the study of Vescovi et al [ 32 ], as compared to substantial between-position differences generally found in male counterparts [ 66 , 67 ]. More specific to the present context, external training load in a first Division Spanish women’s team revealed no significant differences as a function of playing position (central defenders, wide defenders, central midfielders, wide midfielders and strikers) [ 68 ]. Results from a meta-analysis confirm the internal–external training load associations in team sports [ 10 ], thereby again making our result concerning training outcomes being independent of playing position compatible with the literature.…”
Section: Discussionmentioning
confidence: 99%